An improved multicast based energy efficient opportunistic data scheduling algorithm for VANET - Shrivastava, Anurag; Bansod, Prashant; Gupta, Kamlesh; Merchant, Shabbir N. (International journal of electronics and communications, 2018)
A road side unit in VANET is capable of providing various infotainment services. With the increase in demand for data download amongst the vehicular users, power consumption, both at vehicle end and the road side unit is also increasing proportionally. Hence, there is a need for improving energy efficiency as well as the throughput of the system. In this work, we focus on improving energy efficiency and throughput of the road side unit. We propose an improved multicast based energy efficient opportunistic data scheduling algorithm. We estimate optimum data rate and optimum number of users having good channel conditions, thus obviating the need to know the channel state information at the transmitter. The group of users so selected is served by multicasting the service at optimal data rate. Results show that the proposed algorithm is not only energy efficient but also throughput optimal. It is also possible to estimate the maximum throughput accurately and with low search complexity (O(N)) using the proposed method. Simulations are done for two different cases in order to test the flexibility of the algorithm—one, when no new user is entertained until all the initial users get served; two, new users can enter the system in every time slot.